Із досвіду викладання білінгвальних дисциплін майбутнім магістрам у провінційному внз - Ковальчук, А.О.; Kovalchuk, A.O.; Ковальчук, А.А. (Харківський національний університет імені В.Н. Каразіна, Центр міжнародної освіти, 2010)
У статті показана доцільність впровадження білінгвальних курсів у процесі підготовки студентів ОКР „Магістр” та узагальнено рекомендації щодо організації такого навчання і питань методики побудови білінгвальних лекційних курсів із фізичних дисциплін.
From the Experience of Teaching Bilingual Disciplines to the Prospective Masters at a Provincial University
Из опыта преподавания билингвальных дисциплин будущим магистрам в провинциальном ВУЗе
The appropriateness of implementing bilingual courses in the course of teaching master students is introduced in the article. The article contains generalized recommendations as to the organization of education under analysis and some issues concerning the methodology of the curriculum of lecture courses in physics disciplines.
Keywords: bilingual education; master program; physics in English; билингвальное обучение; магистратура; физика на английском языке; білінгвальне навчання; магістратура; фізика англійською мовою